Sosialisasi Pemilahan Dan Pengolahan Sampah Untuk Meningkatkan Sikap Peduli Lingkungan Siswa Sekolah Dasar - Erna Suwangsih; Indah Nurmahanani; Eko Rubiyanto; Aulia Fitri Syahidah; Fitri Rahmida; Lala Amelia; Liya Lisnawati; Yuni Widianingsih (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The development of the globalization era at present leads to technological advancements in various fields, encompassing economics, social aspects, education, and health. Technological progress brings forth both positive and negative impacts on the environment. One of the negative impacts of technological advancement on the environment is environmental degradation resulting in a decline in the quality of the living environment. The environment constitutes a unified system wherein there exist interrelated interactions among living organisms, objects, and resources. An individual's attitude can determine the favorable or unfavorable conditions and situations that occur within the surrounding environment. The environment must be maintained in terms of cleanliness and beauty with a strong sense of responsibility and a heightened awareness in environmental preservation. However, based on observational findings, it is evident that the attitude of environmental concern among students at a certain State Elementary School in Purwakarta is still lacking. To cultivate a sense of environmental concern, a service initiative is conducted with the aim of providing education regarding environmental awareness, particularly for elementary school students. The outcomes obtained from this service initiative prove to be highly beneficial for the students, as they become more conscious of safeguarding and maintaining the environment around them.